2009
DOI: 10.1186/1471-230x-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Development of functional gastrointestinal disorders after Giardia lambliainfection

Abstract: BackgroundFunctional gastrointestinal disorders (FGID) may occur following acute gastroenteritis. This long-term complication has previously not been described after infection with the non-invasive protozoan Giardia lamblia. This study aims to characterize persistent abdominal symptoms elicited by Giardia infection according to Rome II criteria and symptoms scores.MethodsStructured interview and questionnaires 12–30 months after the onset of Giardia infection, and at least 6 months after Giardia eradication, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 26 publications
5
108
0
5
Order By: Relevance
“…The G. intestinalis infection has been found to trigger abdominal symptoms of functional gastrointestinal disorders such as irritable bowel syndrome and functional dyspepsia [16,17,18]. In Egypt, in which Giardia is endemic, the prevalence of G. intestinalis was 44% (96/220) among patients with dyspepsia [3].…”
Section: Discussionmentioning
confidence: 99%
“…The G. intestinalis infection has been found to trigger abdominal symptoms of functional gastrointestinal disorders such as irritable bowel syndrome and functional dyspepsia [16,17,18]. In Egypt, in which Giardia is endemic, the prevalence of G. intestinalis was 44% (96/220) among patients with dyspepsia [3].…”
Section: Discussionmentioning
confidence: 99%
“…Porém, em alguns casos, pode causar danos à mucosa e consequentemente gerar distúrbios gastrointestinais, dos quais a diarreia disabsortiva é o sintoma mais relatado 6,7 . Ocasionalmente, tem sido relatada a associação de infecção por G. lamblia com urticária e prurido 8 , uveíte 9 e até mesmo com sensibilização para antígenos alimentares, o que fez surgir hipóteses de algum nexo causal entre essas doenças e as protozooses 7,10 .…”
Section: Introductionunclassified
“…However, this is unsupported, since many long-term infections are suspected to represent either persisting abdominal symptoms elicited post-Giardia infection or reinfections (176,196,484). The fecal-oral route still remains the most important mode of infection (33), and various studies have found evidence of zoonotic transmission (89,118,237).…”
Section: Giardia Intestinalismentioning
confidence: 99%